Factors Associated with Exclusive Breastfeeeding: Application of PRECEDE-PROCEED Model and Theory of Planned Behavior - Alfianrisa, Anggityas; Salimo, Harsono; Poncorini, Eti (Journal of Maternal and Child Health, 2017)
Background: Exclusive breastfeeding (EBF) is an ideal food for infants aged 0-6 months. EBF is useful for infants, but it is under-implemented. A non profit organization, namely Indonesian Association of Lactating Mothers (AIMI), has been established recently, with an objective to disseminate knowledge and information on breastfeeding and to increase breastfeeding practice in Indonesia. This study aimed to examine factors associated with exclusive breastfeeeding using